Geographic health inequalities in Norway: a Gini analysis of cross-county differences in mortality from 1980 to 2014 - Eirin K. Skaftun; Stéphane Verguet; Ole F. Norheim; Kjell A. Johansson (BMC, 2018)
Abstract Background This study aims at quantifying the level and changes over time of inequality in age-specific mortality and life expectancy between the 19 Norwegian counties from 1980 to 2014. Methods Data on population and mortality by county was obtained from Statistics Norway for 1980-2014. Life expectancy and age-specific mortality rates (0-4, 5-49 and 50-69 age groups) were estimated by year and county. Geographic inequality was described by the absolute Gini index annually. Results Life expectancy in Norway has increased from 75.6 to 82.0 years, and the risk of death before the age of 70 has decreased from 26 to 14% from 1980 to 2014. The absolute Gini index decreased over the period 1980 to 2014 from 0.43 to 0.32 for life expectancy, from 0.012 to 0.0057 for the age group 50-69 years, from 0.0038 to 0.0022 for the age group 5-49 years, and from 0.0009 to 0.0006 for the age group 0-4 years. It will take between 2 and 32 years (national average 7 years) until the counties catch up with the life expectancy in the best performing county if their annual rates of increase remain unchanged. Conclusion Using the absolute Gini index as a metric for monitoring changes in geographic inequality over time may be a valuable tool for informing public health policies. The absolute inequality in mortality and life expectancy between Norwegian counties has decreased from 1980 to 2014.